Optimasi Basis Masker Gel Peel-Off dan Uji Stabilitas Fisik Sediaan Masker Gel Peel-Off dari Ekstrak Daun Sirih Hitam (Piper betle L. VAR. NIGRA): Optimization of Peel-Off Gel Mask Base and Physical Stability Test of Peel-Off Gel Mask from Black Betel Leaf Extract (Piper betle L. VAR. NIGRA) - Nadira Yuli Istiana; Nurul Fitriani; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Gel peel-off masks have many advantages, namely that besides being easy to apply, this masks can also produce good release and penetration of active substances. Black betle (Piper betle L. var. Nigra) is a type of plant that has been studied to have good antibacterial activity against several types of bacteria, including Staphylococcus aureus. The aim of this study was to determine the best formulation for the gel mask and to determine the stability of the preparation of the gel peel-off mask after addition of black betel leaf extract (Piper betle L. var. Nigra). The optimization of the gel-base was carried out by formulating a gel peel- off mask preparation using carbopol in 4 different concentrations, namely F1 0.5%, F2 1%, F3 1.5% and F4 2%, then carried out a physical evaluation of the preparation including organoleptic tests, homogeneity, pH, dispersibility, adhesion, viscosity and drying time. After getting the best gel-base formula, black betle leaf extract was added, and the preparation was again performed for physical evaluation. The result of the optimization of the base gel peel-off mask obtained a base with the characteristics of a transparent white gel, homogeneous, characteristic aroma, thick, pH 5.37, adhesion 18 seconds ? 1 minute, spreading 4,5-7 cm cm, time drying time 14-19 minutes and viscosity of 3,987-26,164 Pa.s. The average results of the physical stability test of the preparation of the gel peel-off mask after the addition of black betle leaf extract were dark green, homogeneous, distinctive rose aroma, thick form, pH 5.6, adhesion 19 seconds, spread 6.4 cm, drying time 17 minutes, viscosity 3.251 Pa.s and absence of syneresis.